Genetic analysis of β1 integrin “activation motifs” in mice - Czuchra, Aleksandra (The Rockefeller University Press, 2006)
Akey feature of integrins is their ability to regulate the affinity for ligands, a process termed integrin activation. The final step in integrin activation is talin binding to the NPXY motif of the integrin β cytoplasmic domains. Talin binding disrupts the salt bridge between the α/β tails, leading to tail separation and integrin activation. We analyzed mice in which we mutated the tyrosines of the β1 tail and the membrane-proximal aspartic acid required for the salt bridge. Tyrosine-to-alanine substitutions abolished β1 integrin functions and led to a β1 integrin–null phenotype in vivo. Surprisingly, neither the substitution of the tyrosines with phenylalanine nor the aspartic acid with alanine resulted in an obvious defect. These data suggest that the NPXY motifs of the β1 integrin tail are essential for β1 integrin function, whereas tyrosine phosphorylation and the membrane-proximal salt bridge between α and β1 tails have no apparent function under physiological conditions in vivo.